Effect of replacing commonly consumed fruit in the United States with berries in the USDA healthy Dietary Patterns: a modeling analysis - Kim S. Stote; Kristi Crowe-White; Leslie Wada (Annals of Medicine)
Introduction A recent review of the evidence suggests that berry consumption may have an effect in reducing cardiovascular disease risk.Objective To assess the nutritional impact of replacing a serving of commonly consumed fruit with a serving of berries in the US Department of Agriculture (USDA) Dietary Patterns: Healthy US-Style (HUS), Healthy Mediterranean-Style (HMS), and Healthy Vegetarian (HV).Methods Using the USDA’s food pattern modeling approach, three 7-day replacement menus were developed for the HUS, HMS, and HV patterns at the 2000-calorie level. The menus included one serving of mixed berries replacing one serving of commonly consumed fruits (apples, bananas, or grapes) while meeting recommendations for other food groups. A total of 2 servings of fruit per day were used in the menus. Nutrient and anthocyanin analyses were conducted on the 7-day menus using ESHA Food Processor: 11.14.x software and the USDA Database for Flavonoid Content of Selected Foods, Release 3.3.Results Replacing a serving of commonly consumed fruit with a serving of berries per day in the 2000 calorie USDA Dietary Patterns resulted in an increase of anthocyanins by 93.8%, with a ≤ 2.0% increase or decrease in calories, macronutrients, fatty acids, and cholesterol. Dietary fiber increased by 4.7% in the HUS and 5.1% in the HMS USDA Dietary Patterns with minimal increases (< 1.5%) in the HV USDA Dietary Patterns. Soluble fiber increased by 10.1%, 5.3%, and 10.2% in the HUS, HMS, and HV USDA Dietary Patterns, respectively. Vitamin C increased by 16% in the HUS, 13.9% in the HMS, and 11.9% in the HV USDA Dietary Patterns.Conclusion The addition of berries to the USDA Dietary Patterns increased beneficial dietary components and nutrients with minimal change in calories, macronutrients, fatty acids, and cholesterol.